TINJAUAN HUKUM TERHADAP BATAS MINIMAL 30% CALON ANGGOTA LEGISLATIF PEREMPUAN YANG DIAJUKAN OLEH PARTAI POLITIK PADA PEMILU LEGISLATIF - Irfandi, Irfandi; Husen, La Ode; Zulkifli Muhdar, Muhammad (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2022)
ABSTRAC This study aims to find out and analyze the legal rules regarding the Minimum Limit of 30% Quota of Female Legislative Candidates proposed by Political Parties and to know and analyze the implications of the application of the minimum 30% quota for female legislative candidates proposed by Political Parties in the Legislative Election. This study uses the Legal Research method with the type of normative legal research, which is a study that examines the law based on statutory regulations. The results of this study show that the opportunity for women's involvement in politics has been wide open when the affirmative action policy was introduced. This policy requires that the quota that must be fulfilled by political parties in compiling the list of candidates for legislative members is 30%. These formal regulations are strengthened by various regulations such as the Election Law No.10/2008, Election Law No.8/2012, PKPU No.7/2013 and Election Law No.7/2017.UU.No.22 of 2007 There are formal legal guarantees for women to be involved in politics is already open, but there are still obstacles faced by women to enter the political sphere, especially as members of the legislature. Affirmative action against women in politics began with the passing of Law Number 12 of 2003 concerning the Election of DPR, DPD, and DPRD. Article 65 paragraph (1) of Law Number 12 of 2003 concerning the Election of DPR, DPD, and DPRD states that: Every Election Contesting Political Party may nominate candidates for Members of DPR, Provincial DPRD, and Regency/Municipal DPRD for each Electoral District with due observance of representation. women at least 30%.